ANALISIS KONFLIKPEGAWAI PADA BAGIAN UMUM DAN PERLENGKAPANSEKRETARIAT DAERAH KABUPATENLAMPUNG TIMUR - Suwandi -; Betty Magdalena (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2020)
Leadership is an important part of management, because leaders must plan and organize the people they lead to achieve the goals set in a participatory manner.At the stage of correlation analysis between autocratic leadership style independent variables (X) and employee conflict dependent variables (Y), the correlation coefficient between the two variables is 0.613, which means there is a strong relationship between autocratic leadership style independent variables (X) and employee conflict dependent variables (Y) in the General Section and Equipment of the Regional Secretariat of East Lampung Regency.